Tourist Knowledge, Pro-Conservation Intentions, and Tourist Concern for the Impacts of Whale-Watching in Las Perlas Archipelago, Panama - Cárdenas, Susana; Gabela-Flores, María Virginia; Amrein, Arielle; Surrey, Katie; Gerber, Leah R.; Guzmán, Hector M. (Frontiers in Marine Science, 2021)
Whale-watching has become an important economic activity for many coastal areas where whales aggregate at certain times of year. Las Perlas Archipelago in Panama, is a breeding ground for humpback whales, where the numbers of both visitors and tour operators have increased in recent years with little compliance and enforcement of regulations. Nevertheless, there is potential to improve whale-watching management at this site and its use as a tool for education and conservation awareness. Our objective was to assess tourist knowledge, perceptions and pro-conservation attitudes related to whale-watching and how this activity is managed in Las Perlas. One hundred and eleven tourists were surveyed in the summer of 2019 after they participated in whale‐watching tours. Our results indicated that in general, respondents had little knowledge about whales and their conservation before a whale-watching trip, however, after the excursion tourists felt they had learned more about whale biology and the regulations for whale-watching. Overall trip satisfaction after whale-watching activities was higher when whale behaviors, including breaching and tail slaps, were observed. The results also showed a lower satisfaction with non-compliance of regulations to reduce impacts of whale-watching, mainly related to the number of boats observing whales at the same time. Both knowledge and concern for lack of compliance seemed to be associated with whale-watching operations that had more formal interpretation activities onboard. The study highlights the importance of whale-watching as a tool for promoting whale conservation through education and the need to improve the enforcement of existing regulations and visitor monitoring to reduce potential whale-watching impacts.